2000
DOI: 10.1603/0022-0493-93.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Novel Extraction of German Cockroach (Dictyoptera: Blattellidae) Fecal Pellets Enhances Efficacy of Spray Formulation Insecticides

Abstract: Methanol extracts of German cockroach, Blattella germanica (L.), fecal pellets have limited use as pheromone attractants in the urban environment because of their unpleasant color and odor. To eliminate these characteristics, a novel aqueous extract of German cockroach feces was formulated. Fetal material was extracted with methylene chloride and mixed with water. The aqueous phase of the extract was colorless and relatively odorless compared with methanol fecal extracts. Aqueous extract was bioassayed and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The present findings are consistent with Albuquerque et al 34 who found that even 15 min exposure of B. germanica to residual deposits of an encapsulated pyrethroid, lambda‐cyhalothrin, caused only 94% mortality. This part of the present research suggests that spray residual formulations might be improved by the addition of arrestants or attractants35, 36 in order to inhibit pest movement and prolong exposure on the treated surface.…”
Section: Discussionmentioning
confidence: 87%
“…The present findings are consistent with Albuquerque et al 34 who found that even 15 min exposure of B. germanica to residual deposits of an encapsulated pyrethroid, lambda‐cyhalothrin, caused only 94% mortality. This part of the present research suggests that spray residual formulations might be improved by the addition of arrestants or attractants35, 36 in order to inhibit pest movement and prolong exposure on the treated surface.…”
Section: Discussionmentioning
confidence: 87%
“…The two-step extraction procedure yields an aqueous solution of the fecal material that is colorless, low odor, and suitable for use indoors. Bioassays conÞrmed that the aqueous extract also exhibits aggregation activity (Miller and Koehler 2000a). Miller and Koehler (2000b) subsequently documented German cockroach trail-following behavior in response to fecal extracts.…”
mentioning
confidence: 97%
“…These characteristics have made the use of fecal extract impractical unless it was contained within traps (i.e., the Woodstream product) or inside bait stations. However, a process described by Miller and Koehler (2000a) was found to eliminate the color and foul odor associated with fecal extracts. The two-step extraction procedure yields an aqueous solution of the fecal material that is colorless, low odor, and suitable for use indoors.…”
mentioning
confidence: 99%